Geometric Morphometric Study of Mandibular Body Morphology in Children: Implications for Forensic Age and Sex Estimation - Pande Made Maha Prathanika; Ammar Rezadin; Siti Aisyah Aminah Rosli; Nurjehan Mohamed Ibrahim; Fahmi Oscandar; Niwa Hafrina; Arofi Kurniawan; Aspalilah Alias (Faculty of Syariah and Law, USIM, 2026)
The mandible is one of the bones that have special characteristics in comparison to other bones. The mandible is the strongest bone on the face and an important part of the forensic profile. The purpose of this study was to identify differences in the morphology of the mandible body related to age and sex in children used on the panoramic radiograph. Eight anatomical landmarks were digitised on 305 panoramic radiographs (159 male and 146 female) using TPSdig2 software. The shape data were analysed with MorphoJ using Generalised Procrustes Analysis (GPA), Principal Component Analysis (PCA), Canonical Variate Analysis (CVA), and Discriminant Function Analysis (DFA). The shape and size differences were tested by Procrustes ANOVA. Two groups (G1 male and G2 female) were used for the determination of sex, while three age groups (3 to 6, 7 to 9 and 10 to 12 years) were tested for age prediction. Morphological variation was visualised with wireframe and lollipop diagrams. The total shape variation was explained by the first four principal components (PC1–PC4) covering 82%. DFA accuracy to classify sex was 64.15% (G1) and 67.12% (G2), and of cross validation was 61.63%, and 63.69%. Inequalities based on age group were generally more accurate: 81 to 87% (Age Group 1) and even up to 93.68% for the older subgroups. Procrustes ANOVA revealed no difference in centroid size for the sexes, but significant differences in shape (p < 0.001). Shape and size variations were both significant between age groups (p < 0.001). Geometric morphometric techniques can demonstrate discriminatory features in mandibular body shape for age and sex. It's a useful screening tool for forensics in cases involving children.